EXPLORING SPATIAL HETEROGENEITY OF LIFE EXPECTANCY IN WEST JAVA PROVINCE USING GEOGRAPHICALLY WEIGHTED REGRESSION - VERA MAYA SANTI; MUHAMAD RIFAN; WIDYANTI RAHAYU (Mathematics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2026)
Life Expectancy Rate (LER) is a key indicator of population health and regional welfare. Significant disparities in LER across districts and municipalities in West Java suggest that the factors influencing life expectancy may vary geographically. Conventional regression models often assume spatial homogeneity and may therefore be inadequate for capturing local variations. This study aims to identify the determinants of LER in West Java by applying Geographically Weighted Regression (GWR) with an adaptive kernel bisquare weighting scheme. Secondary data were obtained from Statistics Indonesia (BPS) of West Java Province and the Open Data Jabar portal. The analysis involved 27 districts and municipalities and examined 11 potential explanatory variables. The results indicate that the influence of predictor variables differs across locations, confirming the presence of spatial heterogeneity in LER determinants. The GWR approach produced 27 local regression models and classified the study area into 10 groups based on similarities in significant factors. Furthermore, the proposed model achieved a coefficient of determination (R²) of 98.86%, indicating a strong ability to explain regional variations in life expectancy. These findings highlight the importance of location-specific policy interventions to improve public health outcomes across West Java.